2011
DOI: 10.1371/journal.pone.0027125
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Performance and Acceptability of Three LED Fluorescent Microscopes in Zambia: Lessons Learnt for Scale-Up

Abstract: The World Health Organization recommends the roll-out of light-emitting diode (LED) fluorescent microscopes (FM) as an alternative to light microscopes in resource-limited settings. We evaluated the acceptability and performance of three LED FMs after a short orientation among laboratory technicians from government health centers in Zambia. Sixteen technicians with varied light microscopy experience were oriented to FMs and divided into groups; each group read a different set of 40 slides on each LED FM (Primo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…These results differ from several previous studies where LED-FM increases an average of 10 % of sensitivity over the conventional ZN technique [610]. Other studies have shown equal sensitivity or low specificity of LED-FM compared to conventional ZN technique [9, 1113]. In these studies, readers had no previous experience with fluorescence microscopy, which is the most likely explanation for sensitivity differences compared with other studies and indicating the importance of adapting training intensity according to the level of operator proficiency.…”
Section: Discussioncontrasting
confidence: 92%
“…These results differ from several previous studies where LED-FM increases an average of 10 % of sensitivity over the conventional ZN technique [610]. Other studies have shown equal sensitivity or low specificity of LED-FM compared to conventional ZN technique [9, 1113]. In these studies, readers had no previous experience with fluorescence microscopy, which is the most likely explanation for sensitivity differences compared with other studies and indicating the importance of adapting training intensity according to the level of operator proficiency.…”
Section: Discussioncontrasting
confidence: 92%
“…Slides should be re-read by experienced technicians with feedback given on discrepant results in real time. Similarly, in Zambia, a high-incidence, resource-limited setting, a study of 16 technicians' proficiency after training which also compared all 3 microscopes showed significant differences among technicians that led to low inter-rater reliability and high misclassification rates that overwhelmed any differences in sensitivity among the LED platforms [14].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies showed relatively little difference in accuracy between commercial LED-based products, 23,28,29,36 although the Lumin (LW Scientific) had lower sensitivity in two out of four studies. Overall user appraisal was high across studies; where assessed, the Primo Star iLED (Carl Zeiss Microscopy) ranked highest in terms of user preference, and the Lumin (LW Scientific) ranked lowest.…”
Section: Review Of Who-endorsed Tb Diagnostic Tests 2006-2012 Microsmentioning
confidence: 91%
“…24,26,[29][30][31] These findings were also confirmed for HIVinfected patients. 32,33 However, three studies reported equal sensitivity 34 or lower specificities 30,35,36 for LED FM compared with ZN. In these studies, readers had no previous experience with fluorescence microscopy, which is the most likely explanation for performance differences compared with other studies.…”
Section: Review Of Who-endorsed Tb Diagnostic Tests 2006-2012 Microsmentioning
confidence: 98%